Asthma and exercise-induced respiratory disorders in athletes. The position paper of the Polish Society of Allergology and Polish Society of Sports Medicine - Gawlik, Radoslaw; Kurowski, Marcin; Kowalski, Marek; Ziętkowski, Ziemowit; Pokrywka, Andrzej; Krysztofiak, Hubert; Krzywański, Jarosław; Bugajski, Andrzej; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
Exercise-induced respiratory symptoms describe acute airway narrowing that occurs as a result of exercise. It includes exercise-induced bronchoconstriction (EIB) and exercise-induced asthma (EIA) issues. To provide clinicians with practical guidelines, a multidisciplinary panel of stakeholders was convened to review the pathogenesis of EIB/EIA and to develop evidence-based guidelines for the diagnosis and treatment. Recommendations for the diagnosis and treatment of EIB were developed. High-intensity exercise in polluted environment (cold air, humidity, contamination, allergens) may increase the risk of EIB and asthma symptoms in athletes. Diagnostic procedures should include history taking, physical examination, atopy assessment and functional tests of the respiratory system. A strong recommendation was made for regular use of inhaled glucocorticosteroids and avoidance of short-acting 2-agonists as the only treatment. The treatment of asthma in athletes should always take into account current anti-doping regulations. This position paper reflects the currently available evidence.